Navigating uncertainty in a nascent ecosystem: How shifting cognitive frames influence an incumbent firm's platform scope strategies - Putra, Fathiro Hutama Reksa; Khanagha, Saeed; Pandža, Krsto; Suárez, Fernando F. (Strategic Management Journal, 2025)
Abstract Research Summary We examine how an incumbent firm navigates internal and external uncertainties when entering a nascent platform ecosystem. Drawing on a longitudinal study of a large telecommunication firm's transition into an evolving IoT ecosystem, we advance a cognitive perspective on platform strategy. We explain how managers' cognitive frames shape platform scope decisions based on shifting assumptions and interpretations of ecosystem dynamics and internal capabilities. Our process model shows how deviations between expected and actual developments trigger changes in managers' attitudes toward uncertainty, thereby shifting their cognitive frames and prompting them to modify platform scope strategies, leading to oscillation between shaping and adapting strategic postures. Our theorization sheds light on the cognitive foundations of platform strategy and the dynamics of incumbent platform transitions in a nascent ecosystem. Managerial Summary Incumbents often enter nascent digital ecosystems by introducing a platform, yet uncertainty complicates decisions about the appropriate platform scope. Our nine‐year study of TELECO’s IoT platform reveals three takeaways. First, scope is not a one‐off decision; it evolves as managers revisit assumptions about opportunities and constraints. Second, scope decision rarely move linearly; firms oscillate between broad and calibrated scopes, creating episodes of overreach and retrenchment. Third, interpretations of uncertainty steer these shifts: reading uncertainty as an opportunity supports shaping bets, whereas interpreting it as a constraint encourages adaptation and selective coopetition. Overall, platform decisions in uncertain ecosystems reflect organizational tensions as firms balance ambitions for dominance against market realities and the actions of ecosystem members.